Social Network Analysis: A useful tool for studying Innovation diffusion processes - Beni Houd, Youssef; El Amrani, Mohamed (Economia agro-alimentare/Food Economy - Open Access, 2021)
In our note, we tried to realise a comprehensive document dedicated to Social Network Analysis, in which we focused on its origin, application and adoption in analysing the diffusion of innovation, with particular attention paid to the agriculture sector, because we believe that farmers can easily exchange knowledge with each other and boost the diffusion of innovation in terms of agricultural techniques. Most of the scientific researches reported in our note in which SNA was applied are carried out in developing countries, we reckon that in these countries information is not usually recorded in a database, and farmers can easily get innovation through their system of acquaintances. We noted that SNA is a flexible and useful tool because it can be applied jointly with several approaches and theories. Through SNA, we can get relevant information about the network to understand how innovation gets shared and to assess the role and importance of different actors involved in the network.